Structural and functional age‐related changes in some facial signs of Chinese men: A pilot study. (17th August 2022) - Ye, Chengda; Flament, Frederic; Wang, Yang; Sun, Hua; Yang, Guancheng; Jiang, Yanwen; Delaunay, Caroline; Saint‐Léger, Didier
Abstract: Objective: The objective of the study was to associate, on the same Chinese male subjects, changes in facial ageing signs with some biomechanical skin properties. Methods: The severities of 20 facial ageing signs of 219 differently aged Chinese men (20–65 years) were graded in blind by trained experts through standardized photographs, using a referential skin Atlas dedicated to Asian men. On each subject, the mechanical properties were assessed on the cheek area (left or right at random) by the validated suction technique Cutometer®. Finally, the skin colour parameters were assessed on images from VISIA‐CR device. Results: Clinically speaking, the severity of almost all facial ageing signs increases from 30 to 65 years, in a linear‐like progression, whereas the 20–30 years shows weak increases. Skin colour shows slight but progressive decreases in Luminance and ITA, whereas the yellow and red components slightly increased between 40 and 65 years. At the exception of skin firmness, the skin mechanical properties show a clear decline during the 30–50 years period and plateau beyond. Conclusion: The present study suggests that the 20–30 years period, albeit more clinically 'silent' than the other periods of age, seems to be an age range during which early alterations of some dermal elements' onset. Deeper in vivo investigating techniques (Echography, Multiphotonic microscopy) are needed to confirm such hypothesis. Abstract : This study associate, on same Chinese male subjects, changes in facial ageing signs zith some biomechanical skin properties. Major outputs suggest that the 20‐30 years period, albeit "silent" clinically, seems to be age range during which early alterations of some dermal elements' onset Résumé: Objectif: Pouvoir associer, sur les mêmes sujets masculins chinois, les modifications des signes de vieillissement faciaux avec certaines propriétés mécaniques du tégument. Méthodes: Les sévérités de vingt signes du vieillissement faciaux de 219 hommes chinois de différents âges (de 20 à 65 ans) ont été évalués en aveugle par des experts entraînés sur des photographies standardisées en utilisant des échelles cliniques de référence pour les hommes asiatiques issues des Atlas du vieillissement. Sur chaque sujet les propriétés biomécaniques ont été enregistrées sur la zone de la joue (droite ou gauche suivant un plan de randomization) avec un appareil de succion validé, le Cutometer®. Enfin, les paramètres coloriels ont été mesurés sur des images enregistrées avec le VISIA‐CR. Résultats: D'un point de vue clinique, la sévérité de la plupart des signes étudiés augmentent de manière linéaire de 30 à 65 ans, tandis qu'entre 20 et 30 ans les augmentations sont faibles. La couleur de la peau présente une faible, mais linéaire, chute de la luminance et de l'ITA, tandis que les composantes jaune et rouge augmentent légèrement entre 40 et 65 ans. A exception de la fermeté de la peau, les propriétés mécaniques présentent une chute importante entre 30 et 50 ans et un plateau ensuite. Conclusion: Cette étude suggère que la période entre 20 et 30 ans, observée comme "silencieuse" d'un point de vue Clinique contrairement aux autres classes d'âge, semble être un moment charnière durant lequel les premières altérations dermiques s'opèrent. De plus amples investigations in vivo usant de techniques d'imageries structurelles (Microscopie Multi‐photonique, Echographie…) seraient nécessaires pour confirmer de tells hypothèses.